Chemical characterization of non‐psychoactive Cannabis sativa L. extracts, in vitro antiproliferative activity and induction of apoptosis in chronic myelogenous leukaemia cancer cells. (2nd February 2022) - Anceschi, Lisa; Codeluppi, Alessandro; Brighenti, Virginia; Tassinari, Riccardo; Taglioli, Valentina; Marchetti, Lucia; Roncati, Luca; Alessandrini, Andrea; Corsi, Lorenzo; Pellati, Federica
Abstract: In this study, extracts from non‐psychoactive Cannabis sativa L. varieties were characterized by means of ultra high‐performance liquid chromatography coupled with high‐resolution mass spectrometry (UHPLC‐HRMS) and their antiproliferative activity was assessed in vitro. The human chronic myelogenous leukaemia cell line K562 was chosen to investigate the mechanism of cell death. The effect on the cell cycle and cell death was analysed by flow cytometry. Proteins related to apoptosis were studied by western blotting. Mechanical properties of cells were assessed using the Micropipette Aspiration Technique (MAT). The results indicated that the cannabidiol (CBD)‐rich extract inhibited cell proliferation of K562 cell line in a dose‐dependent manner and induced apoptosis via caspase 3 and 7 activation. A significant decrease in the mitochondrial membrane potential was detected, together with the release of cytochrome c into the cytosol. The main apoptotic markers were not involved in the mechanism of cell death. The extract was also able to modify the mechanical properties of cells. Thus, this hemp extract and its pure component CBD deserve further investigation for a possible application against myeloproliferative diseases, also in association with other anticancer drugs.